Microplastic Distribution in Beach Sediments: Comparison Between the North and South Waters of East Java Island, Indonesia - Defri Yona; Fahreza Okta Setyawan; Sisylia Eka Narriyah Putri; Feni Iranawati; Muhammad Ariq Kautsar; Atsuhiko Isobe (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research